Somatic diversity among university students in the republic of Belarus = Zróżnicowanie cech somatycznych studentów republiki Białorusi - Gierasiewicz, Anatolij (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper attempts to assess the development of somatic features in students whose study programs include diversified physical activity. The research was carried out in 2011-2012 among 788 male and female students of the years three and four of physical education, humanities, and engineering at the State University of Brest. Martin`s technique was used to measure body lengths, widths, circumferences, skinfolds, and body mass. The material was analyzed statistically. Sexual dimorphism was determined with Mollison`s index.
Keywords: młodzież akademicka; rozwój fizyczny; charakterystyka porównawcza; academic students; physical development; comparative characteristics